EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN GOOGLE SITES TERHADAP HASIL BELAJAR MATEMATIKA KELAS V MADRASAH IBTIDAIYAH MA'HAD AL-ZAYTUN - Suci Ayunda Sari; Dede Indra Setiabudi; Irvan Iswandi (STKIP Subang, 2025)
This study aims to determine the effectiveness of using Google Sites-basedlearning media on students’ mathematics learning outcomes and to analyzestudents’ responses to the use of this media in learning. The method used in thisstudy is a quantitative approach with a type of pre-experimental research design,employing a pretest-posttest design. Data were collected through tests andquestionnaires, with the research subjects being 44 fifth-grade students at MIMa’had Al-Zaytun. Data analysis was conducted using descriptive and inferentialanalysis, with the Paired Sample T-Test. The collected data were analyzed usingSPSS.The results of the analysis showed that the significance value of the hypothesistest was 0.001 (< 0.05), indicating a significant difference between the students’pretest and posttest scores. The average score increased from 61.98 in thepretest to 81.63 in the posttest, and the percentage of learning mastery rosesharply from 23.26% to 76.74%. Additionally, the questionnaire results showedthat the majority of students responded positively and enthusiastically to the use ofGoogle Sites as a learning medium, stating that it made learning more enjoyableand easier to understand.Based on these data, it can be concluded that the use of Google Sites can beeffectively applied in the fifth-grade classroom at MI Ma’had Al-Zaytun and has apositive impact on students’ mathematics learning outcomes.